GROUP WORK STRATEGIES IN EFL CLASSES - Ortikova Ibodatxon; Xaydarova Go’zalxon (Western European Studies, 2024)
This thesis investigates the effectiveness of different group work methodologies in English as a Foreign Language (EFL) class. The study examines how distinctive group work approaches affect dialect learning results and understudy engagement in EFL classrooms. Information was collected through classroom observations, student surveys, and teacher interviews, and analyzed to identify key factors influencing the success of group work in EFL settings. The discoveries suggest that certain group work techniques, such as task-based learning and cooperative learning, have a positive effect on language acquisition and student motivation.
Keywords: group-work; classroom; EFL